Epidemiology of chronic kidney disease and the heightened risk of hepatitis C virus infection in low-resource settings - Nuryati Anik; Budi Setiawan; Catur Wijayanti (Healthcare in Low-resource Settings)
Chronic kidney disease (CKD) is a significant non-communicable disease with varying incidence and prevalence globally. Over the past two decades, it has emerged as one of the leading causes of mortality. In Indonesia, CKD has risen sharply and now represents one of the highest disease-related cost burdens. CKD patients, both men and women, across different age groups, face complex challenges, including the risk of hepatitis C virus (HCV) infection due to hemodialysis (HD). This cross-sectional study investigated 43 CKD patients undergoing HD twice weekly for at least one year at a regional hospital in Yogyakarta, all of whom initially tested negative for HCV. The results revealed that 58.1% of CKD patients were female, with 32.6% aged 55-65 years. Most (60.5%) had completed high school education, and 39.5% were housewives. Interestingly, 69.8% of cases were not primarily caused by kidney-related conditions. Importantly, the longer a patient undergoes HD, the higher their risk of acquiring HCV infection. Although the percentages may vary across different settings, this study highlights the urgent need for targeted infection control measures, particularly in resource-limited healthcare environments where access to preventive strategies may be constrained.